Study of Utilization Of Pakcoy Stems (Brassica Rapa Var. Chinensis) As Sweets With Variations Of Coconut Sugar To Empower The Community Of Ngrombo Tourism Village, Baki, Sukoharjo - Tri Hastiningsih, Wahyu; Prasiwi Citra Resmi (Faculty of Economics and Business, University of Mataram, 2025)
This study aims to examine the manufacture of sweets from pakcoy stems as a diversification of hydroponic waste products in Ngrombo Tourism Village, Sukoharjo. In addition, this study also aims to evaluate the quality of candied pakcoy sticks with coconut sugar variations through organoleptic tests that include aspects of liking, color, taste, aroma, and texture. The method used in this study is an experiment with a quantitative approach. The research was carried out by making candied pakcoy sticks using two variations of sugar, namely coconut sugar and granulated sugar. Confectionery quality data was analyzed using an oragoleptic test to describe the characteristics of respondents, as well as a Posttest Only Control Group to determine the influence of sugar variations on confectionery quality. The results showed that there was a significant influence between sugar variations on the quality of candied pakcoy sticks, especially in the color aspect. Although the differences in the aspects of liking, taste, aroma, and texture were not significant, candied pakcoy sticks with coconut sugar variations were preferred by most respondents compared to sugar variations. This study also shows that the processing of pakcoy stem waste into sweets can increase the economic potential of the people of Ngrombo Village.